Entrepreneurial Contributions to Social Development: Insights from Practitioners and Stakeholders in Phnom Penh, Cambodia - Bunheng Ban; Vithyea You; Pio Sario T (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: The purpose of this study is to assess the contributions of entrepreneurs in Phnom Penh to social development, focusing on four key dimensions: social cohesion, social inclusion, social empowerment, and social security. Methodology: This study employed a quantitative research design using a structured online survey distributed via Google Forms. The survey included Likert-scale items to measure entrepreneurs' contributions to social development. Data were analyzed using descriptive statistics with Statistical Package for the Social Sciences (SPSS) software. Main Findings: The study found that entrepreneurs in Phnom Penh generally perceive themselves as contributing positively to social development, particularly in social cohesion (mean=3.68), social inclusion (mean=3.60), social empowerment (mean=3.71), and social security (mean=3.70). Entrepreneurs emphasized promoting peace, democracy, and inclusivity, with a notable focus on improving the lives of marginalized groups and fostering collaboration with various sectors to address social challenges. Novelty/Originality of this study: This study provides a novel insight into the specific contributions of entrepreneurs in Phnom Penh to social development, with a focus on social cohesion, inclusion, empowerment, and security. It advances existing knowledge by highlighting how entrepreneurs integrate social values into business practices and collaborate with stakeholders to address Cambodia's social challenges, offering new perspectives on entrepreneurship’s role in societal transformation.